(untitled) (Research, Society and Development, 2023)
The objective of this study was to evaluate the chemical-bromatological composition of elephant grass (EG) silages with the addition of acerola by-product (ABP). The experimental design was completely randomized, with five treatments: Treatment 1 = 100% EG; Treatment 2 = 94% EG + 06% ABP; Treatment 3 = 88% EG + 12% ABP; Treatment 4 = 82% EG + 18% ABP and Treatment 5 = 76% EG + 24% ABP, with four replications (silos). EG and ABP were mixed at the time of ensiling. The silos were open at 42 days and samples were collect for chemical analysis. The addition of up to 24% of ABP in EG silage significantly (P<.05) increases the pH, dry matter (DM) and crude protein levels, thus providing fermentations within desirable standards. The estimated dry matter intake, neutral detergent fiber (NDF), ash and ethereal extract of EG silage was not influenced by ABP. Total digestible nutrients, total carbohydrates, hemicellulose and estimated DM digestibility decreased linearly. The high levels of NDF and acid detergent fiber of the ABP compromise the DM digestibility, reducing the nutritional value of the silages.